Biomonitoring of water and waste water - Agrawal, Anju.; Gopal, Krishna (London : Springer [distributor], 2013)
Biomonitoring of water quality is very much essential for assessing the overall health of water bodies and safe supply of drinking water. The chemical nature of toxicant is highly dynamic in environment with time and space whereas biological system can integrate all environmental variables over a large period of time in terms of effect that can be easily measured and quantified. In view of the above, there is a pressing need to determine the water quality of natural resources as well as drinking water based on the standard protocols and guidelines from regulatory agencies.It is clear that the synthetic chemicals are essential for our society to maintain the health and well being of the people. However, there has been a range of detrimental effects on human health and natural environment. In general, we need to improve our management of waste chemicals discharged into the air, water and soil environments. New techniques are needed to predict adverse effects before they occur and for the treatment of wastes. In addition, a range of social, political and economic factors will be needed to be taken into account in order to achieve success.
Measurement of Primary Productivity in Relation to Food Chain -- Aquatic Weeds: Occurrence and Distribution -- Analysis of Phytoplankton and Zooplankton: Qualitative and Quantitative -- Application of Diversity Index in Measurement of Species Diversity -- Challenges of Fish Diversity in Polluted Water -- Biomass Production in Food Chain and Its Role at Trophic Levels -- Concept of Rare and Endangered Species and Its Impact as Biodiversity -- Protected Areas in Relation to Marine Parks and Sanctuaries -- Principles of Statistics and Reporting of Data -- General Principles of Toxicity and Its Application -- Fate of Biotoxins in the Environment and Its Health Implications -- Microbial Toxicity Studies -- Toxic Cyanobacteria in Water and Their Public Health Consequences -- Good Laboratory Practices in Biomonitoring.006m o d
Keywords: Water quality biological assessment; Sewage -- Analysis; Biological monitoring